2020
DOI: 10.1126/science.aba4937
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryonic stem cells self-organize into trunk-like structures with neural tube and somites

Abstract: Post-implantation embryogenesis is a highly dynamic process comprising multiple lineage decisions and morphogenetic changes that are inaccessible to deep analysis in vivo. We found that pluripotent mouse embryonic stem cells (mESCs) form aggregates that upon embedding in an extracellular matrix compound induce the formation of highly organized “trunk-like structures” (TLSs) comprising the neural tube and somites. Comparative single-cell RNA sequencing analysis confirmed that this process is highly analogous to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
224
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(236 citation statements)
references
References 68 publications
(46 reference statements)
10
224
2
Order By: Relevance
“…Some striking examples include, but are in no way limited to, the ability of halved sea urchin embryos to each give rise to a fully formed individual, the ability of the chicken embryo to develop normally after surgical removal of a large portion of the primitive streak, and the formation of monozygotic twins [82,83]. This regulative (or self-organizing) ability of developmental systems fascinates experimental embryologists to this day and has recently come back into focus through observations regarding the ability of embryonic cells to break symmetry and generate patterns when aggregated and cultured as multi-cellular aggregates [84][85][86][87].…”
Section: Tissue Tectonics As a Mediator Of Downward Causation In Developmentmentioning
confidence: 99%
“…Some striking examples include, but are in no way limited to, the ability of halved sea urchin embryos to each give rise to a fully formed individual, the ability of the chicken embryo to develop normally after surgical removal of a large portion of the primitive streak, and the formation of monozygotic twins [82,83]. This regulative (or self-organizing) ability of developmental systems fascinates experimental embryologists to this day and has recently come back into focus through observations regarding the ability of embryonic cells to break symmetry and generate patterns when aggregated and cultured as multi-cellular aggregates [84][85][86][87].…”
Section: Tissue Tectonics As a Mediator Of Downward Causation In Developmentmentioning
confidence: 99%
“…Despite their astonishing complexity, the protocol for gastruloid generation from PSCs is remarkably simple. 3D aggregates are exposed to a pulse of the Wnt agonist CHIR99021 and then allowed to develop without additional exogenous signals (Beccari et al, 2018;Brink et al, 2014;Turner et al, 2017;Veenvliet et al, 2020). Gastruloids contain paraxial mesoderm cells and oscillations of the segmentation clock have been observed using Lfng-Venus mouse ESCs .…”
Section: Gastruloidsmentioning
confidence: 99%
“…In conventional gastruloids, morphogenetic events such as somite formation do not take place (Beccari et al, 2018). However, recent studies have revealed that embedding gastruloids in lowpercentage Matrigel can induce morphogenesis Veenvliet et al, 2020). Under such conditions, one study reported the sequential formation of morphological somites with proper anterior-posterior polarity (i.e., Uncx4.1 and Tbx18 domains) .…”
Section: Gastruloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of multicellular living beings involves morphogenetic processes shaping embryo-fetal structures through self-organized activities of pluripotent stem cells (Veenvliet et al, 2020). The orchestrated movement of cellular groups involves genetic as well as mechanical and molecular interactions between cells and their environment (Thompson 1992; Barriga et al, 2018).…”
mentioning
confidence: 99%